Behaviour of yielding and its components of lines and varieties under different levels of nitrogen (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The objective of the investigation was to evaluate three lines of medium duration /10194, 9677 and 10721 under the effect of the levels 0, 60,101.49 and 144 kg of nitrogen /ha and IACuba – 30 variety was used as a check, the trial was conducted during 2014/2015 dry season a bifactorial design randomised in blocks with 16 variants nitrogen – variety with four replications was used as well as an Hydromorphic antropic, Gley soil in dept, soil samples were taken to 0-20 cm of dept. sowing was done in drill in furrows  separated to 15 cm. Phosphorous and potassium were applied to 100 and 60 kg/ha, and the nitrogen was spplitted in four applications  according to the treatment established. A favourable agronomic efficiency was reached with the use of nitrogen with the levels of 60,101.49 and 144 kgnitrogen/ha. Favourable economic results and net returns of 34193.2 and 34394.4 $/ha, allowing corroborate that the practical application in the productive sphere is based in agronomic application in the productive sphere is based in agronomic and economically
Keywords: lines; rice; nitrogen